2019
DOI: 10.1080/09273948.2019.1657467
|View full text |Cite
|
Sign up to set email alerts
|

A Wide Spectrum of Ocular Manifestations Signify Patients with Systemic Sclerosis

Abstract: Objectives: Systemic sclerosis (SSc) is a rare, chronic connective tissue disease involving multiple organ systems, including the eye. We evaluated the detailed clinical ocular manifestations of outpatients with SSc. Methods: Demographics, disease duration and subtype, nailfold capillaroscopy (NFC) patterns and laboratory parameters encompassing the autoantibody profile of 51 SSc patients were evaluated, and a general ocular examination was performed for each participant. Results: Twenty-nine patients (56.86%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 42 publications
1
42
0
1
Order By: Relevance
“…Ushiyama et al [ 12 ] reported a prevalence of 8% in the control group. In a recent study performed by Szucs et al [ 22 ] 58.9% of the patients had retinal and choroid changes found in the photography of the fundus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ushiyama et al [ 12 ] reported a prevalence of 8% in the control group. In a recent study performed by Szucs et al [ 22 ] 58.9% of the patients had retinal and choroid changes found in the photography of the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…Ushiyama et al [ 12 ] reported higher systolic blood pressure and age in the group of scleroderma patients in comparison to the control group. Szucs et al [ 22 ] did not exclude hypertensive patients. In our study, we excluded patients with diabetes mellitus and smokers, and we did not have any patient with a history of hypertensive crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Gomes and colleagues 3 found the prevalence of glaucoma to be 13.3% (11.1% POAG, 2.2% angle closure glaucoma) but did not investigate for NTG and suggested that systemic vascular disturbances were a potential reason for its occurrence. In a recent study, Szucs and colleagues 4 investigated glaucoma detection based on different diagnostic techniques including IOP measurement, peripapillary RNFL thickness, and automated static perimetry, and they found that approximately one-fifth (21.57%) of the patients suffered from a wide spectrum of glaucoma types including POAG, closed-angle, pigmentary, and NTG. These studies all suggested a glaucomatous propensity and justified long-term follow-up of scleroderma patients to assess the ophthalmological risk.…”
Section: Discussionmentioning
confidence: 99%
“…The higher risk of glaucoma in scleroderma patients is often attributed to generalized vasospasm, which is one of the main features of scleroderma. 1 5 In addition to vasospasm, ischemic changes and local infarction, which are thought to be involved in the pathogenesis of scleroderma, can also increase the risk of glaucoma. 6 , 7 If these ischemic changes and infarction occur in the optic nerve head and peripapillary retina as mentioned above, they may be the main cause of glaucoma predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…Dry eye syndrome (DES) is a dysfunction of the tears and the ocular surface; it is very common and complex, affecting 5-50% of patients, giving rise to symptoms of discomfort, visual disturbances, and tear instability due to an increase in tear osmolarity and the inflammation of the ocular surface [8,9]. Due to increases in video terminal syndrome and office eye disease syndrome, the prevalence of DES rises annually.…”
Section: Introductionmentioning
confidence: 99%